Long-Term Follow-Up Post-Cryosurgery in a Sheep Breast Model - Rabin, Yoed; Julian, Thomas B.; Olson, Peter; Taylor, Michael J.; Wolmark, Norman (Cryobiology, 1999)
This study constitutes the advanced stage of an ongoing project for the development of cryosurgical devices and techniques for breast cryosurgery. The current study focuses on the long-term follow-up post-cryosurgery in a sheep breast model. Results of this study indicate that the cryotreatment site in a sheep breast model cannot be identified up to 5 months post-cryosurgery by means of ultrasound, mammography, or MRI. Histology findings of this study further indicate that there is no gross or microscopic difference between lesions that have been subject to one versus three freeze/thaw cycles. Under either cryosurgical protocol, there is a main cryoinjured region that has uniform destruction of epithelium and healing scar formation and a transition zone of damaged lobules without acini, surrounded by healthy tissues. The cryoinjured region at 5 months post-cryosurgery was found to be about half the diameter of the ultrasound-imaged frozen region during the cryoprocedure. This study shows that, in terms of recovery and regeneration, surgical excision appears to have an advantage over cryosurgery, which results in a more rapid healing process. Based on observations that the cryoinjured region is no smaller than the ultrasound-imaged ice-ball and that the typical thickness of the transition zone is up to 5 mm, a conservative use of the cryosurgical device developed for the current study in an ultrasound-monitored cryoprocedure requires at least 5 mm safety margins of the frozen region radius around the target region.